Consolidating and Upscaling Molecular Research Capacity in Nigeria: On Who's Account? - Chukwudi, Chinwe Uzoma (Frontiers in Research Metrics and Analytics, 2022)
Molecular research and researchers engage in studies that seek to understand the structures, functions, and interactions of biomolecules as the basis for cellular and systemic effects in living organisms. This research approach was made possible by considerable technological advancements that equip researchers with tools to view biomolecules. Although molecular research holds great promises for improving lives and living, the technological requirements and equipment to undertake molecular research are quite expensive, often requiring a heavy start-up capital/investment. In developing countries like Nigeria, where the majority of the population lives below the poverty line and research funding is abysmally low, such heavy investments into research that do not provide immediate solutions to societal problems are difficult. This is mostly due to limited resources available to tackle many urgent and pressing needs, and limited perspective and understanding of policymakers, leading to infrastructural and skilled personnel deficit to support molecular research. Despite all these, the field of molecular research continues to grow exponentially globally, hence, funding and investments into this critical life science research area have become imperative. With the rich biodiversity of humans, animals, and plants in Nigeria, and the huge burden of infectious diseases in the country/region, global advances in genomics and proteomics studies will be incomplete without adequate contribution from Nigeria and sub-Saharan Africa region. This paper examines the progression and challenges of undertaking molecular research in Nigeria, and how Nigerian molecular research scientists are tackling these issues, with recommendations for improved molecular research capacity and output in the country/region.